Enhancement of DNA double-strand break induction and cell killing by K-shell absorption of phosphorus in human cell lines. (1st November 2016) - Tomita, Masanori; Maeda, Munetoshi; Usami, Noriko; Yokoya, Akinari; Watanabe, Ritsuko; Kobayashi, Katsumi
Abstract: Purpose: To investigate an enhancement of DNA double-strand break (DSB) induction and cell killing effect by K-shell ionization of phosphorus atoms and Auger electrons on human cell lines. Materials and methods: Induction of DSB, DNA damage responses, cell cycle distributions, and cell killing effects were investigated after exposures of the cells with monochromatic synchrotron radiation soft X-rays of 2153 and 2147 eV, which were the resonance peak and off peak, respectively, of the K-shell photoabsorption of phosphorus. Results: Higher biological effects in the cells irradiated with soft X-rays at 2153 eV than at 2147 eV were observed in (i) the efficiency of 53BP1/γ-H2AX co-localized foci formation per dose and residual number of foci, (ii) prolonged phosphorylation levels of DSB repair and/or cell cycle checkpoint related proteins and G2 arrest, (iii) the cell killing effects at the 10% survival level of normal human fibroblasts, HeLa cells, and human glioblastoma M059K cells (1.2–1.5 times higher) and that of human ataxia telangiectasia mutated (ATM)-defective cells and glioblastoma DNA-dependent protein kinase catalytic subunit (DNA-PKcs)-defective cells (1.2 times). Conclusion: The yield of DSB and partly less-reparable complex DNA damage induction in human cells was enhanced by K-shell photoabsorption of phosphorus and low-energy Auger electrons.